Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Prioritising domestic locations for marine biosecurity management within a regional vessel network - Cal Faubel; Oliver Floerl; Kyle Hilliam; Simone L Stevenson; Eric A Treml (Biological Conservation, 2025)

Seasonal synchrony between vessel arrivals and larval production may influence the likelihood of biofouling introductions - Simone L. Stevenson; Ian Davidson; Julio Botero; Kay Critchell; Cal Faubel; Kyle Hilliam; Oliver Floerl; Melissa Welsh; Eric A. Treml (Biological Invasions, 2025)
Biofouling of ships and boats is a dominant global transport pathway for marine invasive species. Many biofouling non-indigenous species (NIS) can only be entrained by vessels and subsequently ‘discharged’ during the short-lived but highly mobile larval stage. This means their introduction to new locations is reliant on vessels arriving in suitable habitat while biofouling adults on the hull are spawning. Vessel arrivals and spawning are, however, both transient events. The influence of synchrony between shipping traffic and spawning on introductions of marine NIS is not well understood. Using New Zealand as a case study, we show that seasonality of domestic vessel arrivals is much more prevalent than for international vessel arrivals. Seasonality was identified in 35 of 58 nationwide locations receiving commercial maritime traffic. Seasonal locations most commonly experienced their shipping peaks during spring and summer, while troughs were most common during winter and autumn. This seasonal pattern produces more opportunities for introductions of spring–summer spawners, while potentially limiting introductions of autumn and winter spawners around New Zealand. Our findings indicate the importance of incorporating seasonality into models and risk-assessments of vessel-mediated incursions, and the need for more empirical data on the timing of introduction and entrainment events. There may be an opportunity to optimise surveillance and vector management efforts during periods of peak synchronicity, where the likelihood of incursions is higher.

Corroboration and contradictions in global biodiversity indicators - Simone L. Stevenson; Kate Watermeyer; Simon Ferrier; Elizabeth A. Fulton; Hui Xiao; Emily Nicholson (Biological Conservation, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Using decision science to evaluate global biodiversity indices - Kate E. Watermeyer; Gurutzeta Guillera‐Arroita; Payal Bal; Michael J. Burgass; Lucie M. Bland; Ben Collen; Chris Hallam; Luke T. Kelly; Michael A. McCarthy; Tracey J. Regan; Simone Stevenson; Brendan A. Wintle; et al. (Conservation Biology, 2021)
Global biodiversity indices are used to measure environmental change and progress toward conservation goals, yet few indices have been evaluated comprehensively for their capacity to detect trends of interest, such as declines in threatened species or ecosystem function. Using a structured approach based on decision science, we qualitatively evaluated 9 indices commonly used to track biodiversity at global and regional scales against 5 criteria relating to objectives, design, behavior, incorporation of uncertainty, and constraints (e.g., costs and data availability). Evaluation was based on reference literature for indices available at the time of assessment. We identified 4 key gaps in indices assessed: pathways to achieving goals (means objectives) were not always clear or relevant to desired outcomes (fundamental objectives); index testing and understanding of expected behavior was often lacking; uncertainty was seldom acknowledged or accounted for; and costs of implementation were seldom considered. These gaps may render indices inadequate in certain decision‐making contexts and are problematic for indices linked with biodiversity targets and sustainability goals. Ensuring that index objectives are clear and their design is underpinned by a model of relevant processes are crucial in addressing the gaps identified by our assessment. Uptake and productive use of indices will be improved if index performance is tested rigorously and assumptions and uncertainties are clearly communicated to end users. This will increase index accuracy and value in tracking biodiversity change and supporting national and global policy decisions, such as the post‐2020 global biodiversity framework of the Convention on Biological Diversity.

Matching biodiversity indicators to policy needs - Simone L. Stevenson; Kate Watermeyer; Giovanni Caggiano; Elizabeth A. Fulton; Simon Ferrier; Emily Nicholson (Conservation Biology, 2021)
At the global scale, biodiversity indicators are typically used to monitor general trends, but are rarely implemented with specific purpose or linked directly to decision making. Some indicators are better suited to predicting future change, others are more appropriate for evaluating past actions, but this is seldom made explicit. We developed a conceptual model for assigning biodiversity indicators to appropriate functions based on a common approach used in economics. Using the model, indicators can be classified as leading (indicators that change before the subject of interest, informing preventative actions), coincident (indicators that measure the subject of interest), or lagging (indicators that change after the subject of interest has changed and thus can be used to evaluate past actions). We classified indicators based on ecological theory on biodiversity response times and management objectives in 2 case studies: global species extinction and marine ecosystem collapse. For global species extinctions, indicators of abundance (e.g., the Living Planet Index or biodiversity intactness index) were most likely to respond first, as leading indicators that inform preventative action, while extinction indicators were expected to respond slowly, acting as lagging indicators flagging the need for evaluation. For marine ecosystem collapse, indicators of direct responses to fishing were expected to be leading, while those measuring ecosystem collapse could be lagging. Classification defines an active role for indicators within the policy cycle, creates an explicit link to preventative decision‐making, and supports preventative action.

Testing the presence of marine protected areas against their ability to reduce pressures on biodiversity - Simone L. Stevenson; Skipton N. C. Woolley; Jon Barnett; Piers Dunstan (Conservation Biology, 2020)
Marine protected areas (MPAs) are the preferred tool for preventing marine biodiversity loss, as reflected in international protected area targets. Although the area covered by MPAs is expanding, there is a concern that opposition from resource users is driving them into already low‐use locations, whereas high‐pressure areas remain unprotected, which has serious implications for biodiversity conservation. We tested the spatial relationships between different human‐induced pressures on marine biodiversity and global MPAs. We used global, modeled pressure data and the World Database on Protected Areas to calculate the levels of 15 different human‐induced pressures inside and outside the world's MPAs. We fitted binomial generalized linear models to the data to determine whether each pressure had a positive or negative effect on the likelihood of an area being protected and whether this effect changed with different categories of protection. Pelagic and artisanal fishing, shipping, and introductions of invasive species by ships had a negative relationship with protection, and this relationship persisted under even the least restrictive categories of protection (e.g., protected areas classified as category VI under the International Union for Conservation of Nature, a category that permits sustainable use). In contrast, pressures from dispersed, diffusive sources (e.g., pollution and ocean acidification) had positive relationships with protection. Our results showed that MPAs are systematically established in areas where there is low political opposition, limiting the capacity of existing MPAs to manage key drivers of biodiversity loss. We suggest that conservation efforts focus on biodiversity outcomes and effective reduction of pressures rather than prescribing area‐based targets, and that alternative approaches to conservation are needed in areas where protection is not feasible.